Management of Sturge Weber Syndrome - Irawati Irfani; Sri Hardwiyani (Majalah Oftalmologi Indonesia, 2015)
Background: Sturge-Weber syndrome (SWS) is a neurocutaneous syndrome, characterized by theassociation of facial port-wine hemangiomas in the trigeminal nerve distribution area, with vascularmalformation(s) of the brain (leptomeningeal angioma) with or without glaucoma. It reports a 3 monthold baby girl presented to Pediatric Ophthalmology Unit Cicendo Eye Hospital with Sturge Weber Syndrome.Case Illustration: A 3 month old baby girl presented to Pediatric Ophthalmology Unit Cicendo EyeHospital as a referral from Pediatric Department. Here in, the patient presented with port wine stain,cerebral lesion according to MRI. Her intraocular pressure on first examination was 29.33 mmHg on herright eye and 18.33 mmHg, then she was underwent examination under anesthesia and trabeculotomy-trabeculectomy procedure on December11th 2014. There was a complication of choroidal detachment aftersurgery,and the patient received oral corticosteroid to overcome the problem.On the last visit,this patient presented with controlled intraocular pressureand minimal abnormality in the retina.Conclusion:Treatment for Sturge Weber Syndrome usually symptomatic. Treatment of choice for glaucoma due to Sturge Weber Syndrome is surgical intervention rather than medical therapy.Keywords: Sturge-Weber syndrome, glaucoma